Kouzes Posner's Leadership Strategy by The Principal in Developing Technology-Based Learning Innovations in The Era of Society 5.0. - Ulum, Dahlia; Suyud (Jurnal Administrasi Pendidikan Islam, 2026)
This study aims to analyze the leadership strategies of the principals of State Elementary Schools in Nganjuk District in developing technology-based learning innovations by referring to the theory of 5 leadership approaches by Kouzes & Posner; (1) Model The Way, (2) Inspire a Shared Vision, (3) Challenge the Process, (4) Enable Others to Act, (5) Encourage the Heart. This study uses a qualitative research method with the type of field study research, the researcher examines in depth the leadership strategy of the principal of SDN 1 Ganungkidul and the principal of SDN Kedungdowo as a school that has implemented technology-based learning in Nganjuk District, Nganjuk Regency. Data collection techniques using interviews, observation and documentation, data analysis techniques apply the Miles, Huberman and Saldana models which consist of; data collection, data condensation, data presentation and drawing conclusions or data verification. The research informants were namely 6 people; 1 principal, 1 class teacher at each grade level, and 1 student each grade 3 and grade 6 from SDN 1 Ganungkidul and SDN Kedungdowo. The research results show that the principal at SDN 1 Ganungkidul uses a transformational leadership, which strongly encourages innovation and experimentation in teacher technology use. This includes providing intensive training and providing access to the latest technology tools and resources. In contrast, the principal at SDN Kedungdowo applies a participatory leadership by involving teachers in decision-making regarding the technology used.